Potential Anthelmintic and Antioxidant Activities of Jasminum fruticans L. and Its Phytochemical Analysis - Esra Küpeli Akkol; Esma Kozan; Hilal Bardakci; Timur Hakan Barak; Sara Khalilpour (Pharmaceutical Sciences, 2022)
Background: Ethnobotanical investigations conducted in Turkey demonstrated that Jasminum fruticans L. extract and fruit juice had been used against parasites in animals. In this study, the possible antihelmintic activity of various J. fruticans extracts contributing to its traditional use, was relatively assessed. In addition, the antioxidant potentials and phytochemical composition of the extracts were investigated since there is a relationship between helminthiasis, oxidative stress and phenolic metabolites. Methods: In this study, aerial parts of J. fruticans were subsequently extracted using n-hexane, ethyl acetate (EtOAc) and methanol (MeOH). In vivo anthelmintic activity of the extracts was compared with albendazole used as a reference in adult earthworms. Various methods, including free radical scavenging and metal-related activity assays, were used to assess the antioxidant capacity of the above-mentioned extracts. Assessment of phenolic composition was accomplished through total phenolic, phenolic acid, and flavonoid content assays as well as liquid chromatography-mass spectrometry (LC-MS/MS) using multiple reaction monitoring (MRM) scan modes. Further chlorogenic acid (3-O-caffeoylquinic acid) contents of extracts were quantified using high-performance thin-layer chromatography (HPTLC). Results: Between all tested extracts, MeOH extract at a quantity of 50.0 mg/mL, paralysed worms in 8.1 min and killed them in 12.8 min, showing a high anthelmintic effect similar to albendazole. Similarly, in vitro DPPH radical scavenging activity, cupric ion reduction and total antioxidant capacity experiments demonstrated that MeOH extract had significant antioxidant activity. Further phytochemical screening showed that MeOH extract was richer regarding phenolic metabolites. Chlorogenic acid, ferulic acid, caffeic acid and gallic acid were only detected in the MeOH extract. Conclusion: Results justify and support the use of J. fruticans in traditional medicine as an anthelmintic agent. Furthermore, a positive correlation was found between the strong antioxidant capacity along with the phenolic composition determined in the MeOH extract and anthelmintic activity.